EKSISTENSI RUANG PUBLIK DI BANYUWANGI (Studi Kasus Forum Masyarakat Tolak Tambang Emas Tumpang Pitu “ForBanyuwangi” Desa Sumberagung, Kecamatan Pesanggaran, Kabupaten Banyuwangi) (The Commercium, 2022)
ForBanyuwangi or Banyuwangi People's Forum is a community group that rejects the existence of a gold mine in the Tumpang Pitu mountains. This forum consists of various groups, including environmental activists, students, farmers, fishermen and even artists. ForBanyuwangi as a public sphere which is a portal for sharing any information about Agrarian and Ecological conditions, this portal is managed in a participatory manner by anyone who cares and wants to share information in Banyuwangi, as well as part of the effort to realize citizen journalism in Banyuwangi, (forbanyuwangi. org). Seeing this problem, the problem formulation in this study is how the existence of ForBanyuwangi public sphere as a community forum that rejects the Tumpang Pitu gold mine in Banyuwangi. This research was conducted through a qualitative approach with this type of critical research. Sources of data obtained are the results of observations and in-depth interviews. In addition, the data obtained are also from official data from ForBanyuwangi, books, journals, papers, articles and existing research results that are relevant to this research. The theory used in this research is the theory of public sphere put forward by Jurgen Habermas. Public sphere theory explains that the media is used to communicate information and views, where people meet, chat and discuss what is the subject of conversation. Keyword : ForBanyuwangi, Public Sphere, Gold Mine